Produtividade e Valor nutritivo de Urochloa brizantha cv. Piatã e Qualidade do Solo em Sistemas Silvipastoris na Região Central de Minas Gerais - Elwira Daphinn Siiva Moreira (2018)
The presence of trees in silvopastoral systems (SPS) can affect forage production, structural, characteristics bromatological and environmental sustainability in these systems. The objective of this study was to evaluate the productive parameters and nutritional value of Urochloa brizantha cv. Pipe, soil quality, as well as light interception in silvopastoral systems with different tree densities and years of implantation. The trial conducted at Embrapa Milho and Sorgo, in the Sete Lagoas city, Minas Gerais. The experimental design was completely randomized, with four replications. The treatments consisted of: silvopastoral systems with U. brizantha Piatã and Eucalyptus grandis GG100, implanted in 2009; (SPS1) with 333 ha-1 trees and (SPS2) with 166 ha-1 trees and in 2011; (SPS3) with 333 ha-1 trees (SPS4) with 166 ha-1 trees. In addition to the silvopastoral systems, in spatial arrangements 15 x 2 and 15 x 4 m, a pasture with the same forage in full sun (SP) implemented in 2009 and a area Transitional Semidecidual Seasonal Forest for Cerrado. Samples were taken at distances from the tree component of 0.5; 1.25; 3 and 7 m. At each 28 days, the forage was collected in four replicates using a 1 square meter metal square. The productivity of the whole plant and fractions were determined: leaf, stem and dead material. The production of dry mass, leaf blade ratio, nutritive value, and light interception were evaluated. Photosensitivity radiation was measured using the ceptometer. Soil samples were collected at depths 0-5, 5-10, 10-20, 20-40, 40-60, 60-100 cm for carbon stock, and 0-5 and 60-100 cm for microbiological analyzes: enzymatic activities, metabolic, microorganism population ground, genetic diversity (0.5 and 7 m between Eucalyptus tree). ANOVA and means comparison were performed by the Tukey test with = 0.05. The dry matter prodution in the Piatã grass showed an effect of systems for whole plant, and the production of the grazing (405 day) foi was 13513.25 kg ha-1 year-1 in the SPSs and 28533 kg DM ha-1 year-1 in the SP. The thinning of 50% of the trees in the SPSs did not present significant effect on the PARi and forage production. The five-to-seven-year SPS implementation did not affect PARi in sub-soils, however, causing reductions in forage yield and quality. Increasing shading over time stimulated the increase in mean canopy height. The leaf: stem ratio of the grass was affected by shading in the SSP system. The forage fractions did not change by the reduction of the PARi in the SPS forage when compared to PS (P> 0.05). The silvopastoral systems promoted increases in CP, DM and fiber reduction in relation to PS pasture. As for the biological attributes (UR, BRS, H and genetic diversity) in the soils, there was a significant effect (P <0.05) between the evaluated systems compared to native vegetation, except for distances from the eucalyptus line, which did not differ statistically P> 0.05), although, in terms of genetic diversity in the distance, the distinction was mainly found in functional fungi. The carbon stock in the soil showed an effect between systems (P epasture. The association of trees and pasture in spite of the reduction in 53% of forage production shows promise with good results in the bromatological aspects, improvements in the quality of the soil. Besides contributing to environmental services such as expansions in the carbon stock in the soil and provide improvements in soil quality by increasing the activity of the soil microbiota